Determination of the absolute accuracy of UK chamber facilities used in measuring methane emissions from livestock - Gardiner, T.D.; Coleman, M.D.; Innocenti, F.; Tompkins, J.; Connor, A.; Garnsworthy, P.C.; Moorby, J.M.; Reynolds, C.K.; Waterhouse, A.; Wills, D. (Elsevier, 2015)
Respiration chambers are one of the primary sources of data on methane emissions from livestock. This paper describes the results from a coordinated set of chamber validation experiments which establishes the absolute accuracy of the methane emission rates measured by the chambers, and for the first time provides traceability to international standards, assesses the impact of both sensor and chamber response times on measurement uncertainty and establishes direct comparability between measurements made across different facilities with a wide range of chamber designs. As a result of the validation exercise the estimated absolute uncertainty associated with the overall capability across all facilities reduced from 25.7% (k=2, 95% confidence) before the validation to 2.1% (k=2, 95% confidence) afterwards.